KOMPARASI PENDAPATAN USAHATANI PADI DENGAN SAYURAN PADA MUSIM TANAM II DI LAHAN SAWAH IRIGASI DESA SUMEDANG SARI BUAY MADANG TIMUR - Aisah (Jurnal Bakti Agribisnis, 2015)
The purpose of this research is to: (1) To find out what underlies irrigated paddy farmers to grow vegetables during planting season II (technically and financially) in Sumedang Sari Village, East Buay Madang District, OKU Timur Regency, (2) Rice and vegetable farming in Sumedang Sari Village, Buay Madang Timur District. Determination of location is done purposively (Purposive) with the reason in Sumedang Sari Village is one of the villages that have rice farming and some of them are farming in irrigated rice field. This study was conducted from May to June 2013. The study found that farmers' perceptions of their farming (rice and vegetables) and the positive impact of the farming on paddy fields. From the perception of farmers perception of rice obtained an average score of 14.20 and 56.80% percentage that entered on neutral criteria. As for the perception of vegetable farmers obtained an average score of 17.50 and 70.00% percentage that entered on the criteria agreed, which means that vegetable farming has a positive impact on the fertility of paddy fields. And from result of analysis of rice farming obtained R / C ratio equal to 1,50, while result of analysis of vegetable farming obtained R / C ratio equal to 3,05. From the analysis of perception and R / C value, the ratio of vegetable farming is superior to rice farming. Revenue of paddy farming is Rp. 5,032,800 LG / MT or Rp. 1.258.200 LG / Bln or Rp. 6,150,926 Ha / Month and the cost of Rp. 3.375.199,17 LG / MT or Rp. 843.799,79 LG / Bln or Rp. 4.107.326,43 Ha / Bln, then the income of rice farming is Rp. 1.657.600,83 LG / MT or Rp. 414.400,21 LG / Bln or Rp. 2,043,599,50 Ha / Bln. As for the acceptance of vegetable farming Rp. 17.569.500 LG / MT or Rp. 3.817.984,09 LG / Bln or Rp. 18,392,939.77 Ha / Month and the cost of Rp. 5.856.209,67 LG / MT or Rp. 1.261.602,66 LG / Bln or Rp. 6,087,723.43 Ha / month, then the income of vegetable farming income is Rp. 11.713.290,33 LG / MT or Rp. 2.556.381,43 LG / Bln or Rp. 12.305.216,38 Ha / Bln. From the average income income, vegetable farming income is higher than the income of rice farming. While the resulting income difference of Rp. 10,055,689,5 LG / MT or Rp. 2.141.981,22 LG / Bln or Rp. 10,261,616.88 Ha / Bln.